Diffusion source for neodymium-iron-boron magnet, preparation method of diffusion source and treatment method of magnet
By using copper or copper alloy foil on the iron boron magnets as the diffusion source, attach rare earth particles and non -rare earth metal or alloys, and perform heat treatment and stress solidification, solving The problem realizes efficient diffusion and modification and optimizing magnetic performance.
Patent Information
- Application Number
- CN202411521046.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
While increasing the coercive force of neodymium iron boron magnets and reducing the amount of rare earth elements, it is difficult to effectively control the residual magnetism, maximum magnetic energy production and squareness of the magnets, and the preparation of the diffusion source film layer is easily limited by the magnet specifications and pores. The rate is large, affecting the diffusion effect.
The use of copper or copper alloy foil as the substrate of the diffusion source, attached to rare earth particles, non -rare earth oxides, and non -rare earth metals or alloys. And selectively diffuse and modify.
It significantly improves the stubborn force of the iron boron magnet, reduces the amount of rare earth elements, optimizes the magnetic, maximum magnetic energy accumulation and squareness of the magnet, and improves the activity of the diffusion effect and the diffusion source.
Smart Images

Figure BDA0005108052710000141 
Figure BDA0005108052710000151 
Figure BDA0005108052710000161
Abstract
Description
Technical Field
[0001] The invention relates to a diffusion source for a neodymium iron boron magnet and a preparation method thereof and a magnet processing method. Background Art
[0002] NdFeB permanent magnet materials have high coercivity and remanence. Grain boundary diffusion technology can improve the magnetic properties of NdFeB permanent magnet materials.
[0003] CN118675837A discloses a method for preparing a rare earth permanent magnet material, wherein a heavy rare earth slurry is arranged on a first surface of a first permanent magnet material, and the heavy rare earth slurry includes copper powder, heavy rare earth alloy powder, epoxy resin glue and solvent; the heavy rare earth slurry on the first surface of the first permanent magnet material is cured, the first permanent magnet material after the curing treatment is subjected to diffusion heat treatment, and the first permanent magnet material after the diffusion heat treatment is subjected to aging heat treatment to obtain a rare earth permanent magnet material. The slurry containing heavy rare earth is directly coated on the surface of the magnet, and the uniformity of the film thickness is difficult to control, the load is low, and the film coating process is easily restricted by the magnet specification. For example, a non-planar magnet cannot obtain a high-quality diffusion source film layer with uniform thickness. In addition, the heavy rare earth slurry contains a large amount of organic matter, which will have an adverse effect on the performance of the magnet after diffusion, and the pores between the copper powder and the heavy rare earth alloy powder in the slurry are large. After the organic matter is removed, the contact area between the metal particles is small, and the alloying rate is low, which affects the diffusion effect.
[0004] CN115116728A discloses a grain boundary diffusion method for anisotropic NdFeB magnets, wherein a copper coating with a thickness of 0.1 to 1 μm is deposited on the surface of a sintered NdFeB magnet that does not contain copper by electroplating; a diffusion source powder is mixed with a binder and an organic solvent to prepare a diffusion source slurry, wherein the diffusion source powder is a powder containing a heavy rare earth element, and the heavy rare earth element is at least one of Dy or Tb. The diffusion source slurry is evenly coated on the copper coating on the rare earth surface, the magnet covered with the diffusion source slurry is dried, and then subjected to grain boundary diffusion treatment. In this method, the preparation of the diffusion source film layer is easily restricted by the specifications of the magnet, and the electroplated copper is used to isolate the pollution of organic matter relative to the magnet, but the problem faced in the rare earth slurry film layer coverage is not solved, that is, the problem faced in preparing the rare earth slurry film layer on the surface of the magnet is the same as that faced in preparing the rare earth slurry film layer on the surface of the magnet measured by the electroplated copper film. The undensified diffusion source powders cannot be in close contact with each other, and the porosity is large after the organic phase is removed; the electric field distribution at different positions of the magnet is uneven during electroplating, which easily causes the thickness of the deposited copper film to be different, affecting the performance control of the diffusion magnet; during grain boundary diffusion treatment, the content of binder and organic solvent is too high, affecting the diffusion effect.
[0005] CN114717496A discloses a diffusion source for R-Fe-B rare earth permanent magnet materials, comprising heavy rare earth metal and auxiliary metal elements, wherein the heavy rare earth metal element is one or more of Dy, Tb and Ho, and the auxiliary metal element is one or more of Cu, Al and Ga, wherein the auxiliary metal element content accounts for 1-10% of the total mass, and the porosity of the diffusion source is 30-50%. In this method, the powder is rolled to prepare the diffusion source, which can avoid the restriction of the magnet specification on the preparation of the diffusion source film layer, but the porosity of the diffusion source is still large. The thickness of the thin plate prepared by rolling is 2mm, that is, 2000 microns, which is far too much as a diffusion source, which is not conducive to the efficient use of heavy rare earth elements, and the oversaturated diffusion is easy to deteriorate the magnet performance, and the actual diffusion effect is not good. The heavy rare earth content in the rolled composite diffusion source is high, and the cost is high. Summary of the invention
[0006] One object of the present invention is to provide a diffusion source for NdFeB magnets, which can significantly improve the coercivity of NdFeB magnets. Furthermore, the diffusion source has little effect on the remanence, maximum magnetic energy product, squareness, etc. of the magnets. Furthermore, the diffusion source can reduce the amount of rare earth elements used and selectively diffuse and modify NdFeB magnets.
[0007] Another object of the present invention is to provide a method for preparing a diffusion source, which can improve the bonding force between the attachment and the foil substrate and reduce the porosity between the attachments. Furthermore, the preparation method can effectively reduce the content of impurity elements in the diffusion source, ensure the activity of the diffusion source, and improve the diffusion effect.
[0008] Another object of the present invention is to provide a method for treating NdFeB magnets, which can effectively improve the coercivity of NdFeB magnets. Furthermore, the method has little effect on the remanence, maximum magnetic energy product, squareness, etc. of the magnets.
[0009] In one aspect, the present invention provides a diffusion source for NdFeB magnets, comprising a copper or copper alloy foil and an attachment, wherein the attachments are attached to the upper and lower surfaces of the copper or copper alloy foil, respectively, and the attachments include rare earth particles, non-rare earth oxides, and non-rare earth metals or alloys;
[0010] The rare earth element in the rare earth particles is selected from one or more of terbium, dysprosium, praseodymium, and neodymium, and contains at least one of terbium and dysprosium; the rare earth particles are selected from one or more of rare earth hydride particles, rare earth fluoride particles, rare earth single substance particles, and rare earth alloy particles; the content of the rare earth particles is 10 to 30 parts by weight;
[0011] The non-rare earth oxide is selected from one or more of aluminum oxide and magnesium oxide; the content of the non-rare earth oxide is 0.1 to 5 parts by weight;
[0012] The non-rare earth element in the non-rare earth metal or alloy is selected from one or more of copper, aluminum, magnesium, iron, zirconium, niobium, gallium, zinc, cobalt, and silicon, and the non-rare earth metal or alloy contains at least one of copper and aluminum; the amount of the non-rare earth metal or alloy is 0.3 to 5 parts by weight.
[0013] According to the diffusion source of the present invention, preferably, the total content of terbium and dysprosium in the rare earth particles is greater than or equal to 12wt%, and the total content of rare earth elements is greater than or equal to 42wt%;
[0014] The total content of copper and aluminum in the non-rare earth metal or alloy is greater than or equal to 15 wt %.
[0015] According to the diffusion source of the present invention, preferably, the copper or copper alloy foil has a thickness of 1 to 100 μm;
[0016] The rare earth particles have a D 50 The particle size of the non-rare earth oxide is 200-450 mesh, and the D 50 1~20μm.
[0017] According to the diffusion source of the present invention, preferably, the rare earth particles contain non-rare earth metal elements, and the non-rare earth metal elements are selected from one or more of copper and aluminum.
[0018] In another aspect, the present invention provides a method for preparing the above diffusion source, comprising the following steps:
[0019] (1) coating a diffusion source slurry containing rare earth particles, non-rare earth oxides, non-rare earth metals or alloys, a binder and an organic solvent on the upper surface and the lower surface of a copper or copper alloy foil to obtain a supported material;
[0020] (2) The supported object is heat treated while applying pressure to the upper and lower surfaces of the supported object to obtain a diffusion source.
[0021] According to the preparation method of the present invention, preferably, step (2) comprises the following steps:
[0022] While applying a pressure of 5 to 80 MPa to the upper and lower surfaces of the supported object, the supported object is cured at 80 to 160° C. for 1 to 7 minutes to obtain a diffusion source.
[0023] According to the preparation method of the present invention, preferably, step (2) comprises the following steps:
[0024] While applying a pressure of 5 to 80 MPa to the upper and lower surfaces of the load, the load is cured at 80 to 160° C. for 1 to 7 minutes to obtain a cured product; the cured product is degreased at 230 to 290° C. for 15 to 90 minutes to obtain a diffusion source.
[0025] According to the preparation method of the present invention, preferably, while applying a pressure of 1 to 10 MPa to the upper and lower surfaces of the solidified object, the solidified object is degreased at 230 to 290° C. for 15 to 90 minutes to obtain a diffusion source.
[0026] According to the preparation method of the present invention, preferably, the thickness of the support is 30-150 μm; and the thickness of the diffusion source is 60%-95% of the thickness of the support.
[0027] In another aspect, the present invention provides a method for processing a NdFeB magnet, comprising the following steps:
[0028] Performing heating diffusion and aging treatment on a NdFeB magnet having at least a portion of its surface covered with the diffusion source to obtain a treated magnet;
[0029] The heating diffusion conditions are as follows: the primary diffusion temperature is 600-900°C, the primary diffusion time is 60-240min, the secondary diffusion temperature is 850-960°C, and the secondary diffusion time is 200-500min;
[0030] and optionally, pre-diffusion is performed before the primary diffusion, the pre-diffusion temperature is 250 to 480° C., and the pre-diffusion time is 10 to 100 minutes;
[0031] The aging treatment conditions are as follows: the aging treatment temperature is 450-620°C, and the aging treatment time is 80-350min.
[0032] The diffusion source of the present invention can significantly improve the coercive force of the NdFeB magnet. Furthermore, the diffusion source has little effect on the remanence, maximum magnetic energy product, squareness, etc. of the magnet. Furthermore, the diffusion source can reduce the amount of rare earth elements used and selectively diffuse and modify the NdFeB magnet. The preparation method of the diffusion source of the present invention can improve the bonding force between the attachment and the foil substrate and reduce the porosity between the attachments. Furthermore, the preparation method can effectively reduce the content of impurity elements in the diffusion source, ensure the activity of the diffusion source, and improve the diffusion effect. The processing method of the NdFeB magnet of the present invention can effectively improve the coercive force of the NdFeB magnet. Furthermore, the processing method has little effect on the remanence, maximum magnetic energy product, squareness, etc. of the magnet. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited thereto.
[0034] <Diffusion Source for NdFeB Magnets>
[0035] The diffusion source of the present invention comprises copper or copper alloy foil and attachments. The attachments are attached to the upper surface and the lower surface of the copper or copper alloy foil.
[0036] In the present invention, the copper or copper alloy foil is preferably a copper foil. The copper or copper alloy foil is selected from one or more of a non-porous foil, a foil with a mesh structure, and a foam metal foil. Preferably, the copper or copper alloy foil is a non-porous foil.
[0037] The thickness of the copper or copper alloy foil may be 1 to 100 μm, preferably 3 to 40 μm, and more preferably 5 to 30 μm. In certain embodiments, the thickness of the copper or copper alloy foil is 20 to 25 μm.
[0038] The attachment of the present invention includes rare earth particles, non-rare earth oxides and non-rare earth metals or alloys. In some embodiments, the attachment is composed of rare earth particles, non-rare earth oxides and non-rare earth metals or alloys. The rare earth particles, non-rare earth oxides and non-rare earth metals or alloys in the attachment are uniformly dispersed on the copper or copper alloy foil.
[0039] In the present invention, the rare earth element in the rare earth particles is selected from one or more of terbium, dysprosium, praseodymium, and neodymium, and contains at least one of terbium and dysprosium. In the rare earth particles, the total content of terbium and dysprosium is ≥12wt%; preferably, the total content of terbium and dysprosium is 30-98wt%; more preferably, the total content of terbium and dysprosium is 50-75wt%. In the rare earth particles, the total content of rare earth elements is ≥42wt%; preferably, the total content of rare earth elements is 60-99wt%; more preferably, the total content of rare earth elements is 90-96wt%.
[0040] In the present invention, the rare earth particles can be selected from one or more of rare earth fluoride particles, rare earth hydride particles, rare earth element particles, and rare earth alloy particles. Preferably, the rare earth particles are selected from one or more of rare earth hydride particles and rare earth alloy particles.
[0041] The rare earth fluoride can be selected from one or more of terbium fluoride, dysprosium fluoride, praseodymium fluoride and neodymium fluoride; preferably, the rare earth fluoride is selected from one or more of terbium fluoride and dysprosium fluoride.
[0042] The rare earth hydride may be selected from one or more of terbium hydride, dysprosium hydride, praseodymium hydride and neodymium hydride; preferably, the rare earth hydride is selected from one or more of terbium hydride and dysprosium hydride.
[0043] The rare earth element may be selected from one or more of terbium, dysprosium, praseodymium and neodymium. Preferably, the rare earth element is selected from one or more of terbium and dysprosium.
[0044] Rare earth alloys can be alloys formed between rare earth elements, or alloys formed between rare earth elements and non-rare earth elements. Rare earth alloys can be binary alloys, ternary alloys, or quaternary alloys. The non-rare earth elements in the rare earth alloys can be selected from one or more of copper and aluminum.
[0045] In the rare earth alloy, the content of copper may be 12 to 28 wt %, preferably 16 to 21 wt %.
[0046] In the rare earth alloy, the content of aluminum may be 2 to 6 wt %, preferably 3.5 to 5 wt %.
[0047] In the rare earth alloy, the content of terbium may be 10-98 wt %, in some embodiments, the content of terbium is 20-40 wt %, and in other embodiments, the content of terbium is 90-97 wt %.
[0048] In the rare earth alloy, the content of praseodymium may be 20 to 80 wt %, preferably 30 to 60 wt %.
[0049] In the rare earth alloy, the content of dysprosium element may be 50 to 85 wt %, and more preferably 60 to 70 wt %.
[0050] In some embodiments, the rare earth alloy particles are terbium aluminum alloy particles. In other embodiments, the rare earth alloy particles are praseodymium terbium aluminum alloy particles. In still other embodiments, the rare earth alloy particles are praseodymium dysprosium aluminum alloy particles.
[0051] D of rare earth particles 50 ≤10μm; preferably, D 50 is 0.5 to 8 μm; more preferably, D 50 1~3μm.
[0052] The content of the rare earth particles may be 10 to 30 parts by weight, preferably 15 to 25 parts by weight. In certain embodiments, the content of the rare earth element-containing particles is 16 to 18 parts by weight.
[0053] The non-rare earth oxide is selected from one or more of aluminum oxide and magnesium oxide. Preferably, the non-rare earth oxide is aluminum oxide.
[0054] The non-rare earth oxide can be used in the form of powder. The particle size of the non-rare earth oxide can be 200-450 meshes, preferably 250-350 meshes.
[0055] The amount of the non-rare earth oxide may be 0.1 to 5 parts by weight, preferably 0.8 to 2 parts by weight, and more preferably 1 to 1.5 parts by weight.
[0056] The non-rare earth metal element in the non-rare earth metal or alloy of the present invention is selected from one or more of copper, aluminum, magnesium, iron, zirconium, niobium, gallium, zinc, cobalt, and silicon, and the non-rare earth metal or alloy contains at least one of copper and aluminum. Preferably, the non-rare earth metal or rare earth metal must contain aluminum. Preferably, the non-rare earth metal or alloy is selected from one of aluminum, aluminum-gallium alloy, aluminum-cobalt alloy, aluminum-zinc alloy, aluminum-silicon alloy, and aluminum-magnesium alloy.
[0057] In the non-rare earth metal or alloy, the total content of copper and aluminum is 15-90wt%. In some embodiments, the total content of copper and aluminum is 20-55wt%, preferably 30-50wt%. In other embodiments, the total content of copper and aluminum is 80-85wt%.
[0058] In the non-rare earth metal or alloy, the content of other metal elements except copper and aluminum can be 10-85wt%. In some embodiments, the content of other metal elements is 30-60wt%. In other embodiments, the content of other metal elements is 40-50wt%.
[0059] In the copper-aluminum alloy, the copper content may be 70-90 wt%, preferably 75-88 wt%, more preferably 75-85 wt%, and the aluminum content may be 10-30 wt%, preferably 14-26 wt%, more preferably 16-26 wt%.
[0060] The non-rare earth metal or alloy may be used in the form of a powder. 50 It can be ≤20μm; preferably, D 50 1 to 15 μm; more preferably, D 50 2~8μm.
[0061] The content of the non-rare earth metal or alloy may be 0.5 to 3 parts by weight, preferably 0.8 to 2 parts by weight, and more preferably 1 to 1.5 parts by weight.
[0062] The thickness of the diffusion source may be 12 to 85 μm, preferably 20 to 60 μm, and more preferably 30 to 50 μm.
[0063] The attachment formed by the present invention has high activity when diffusing NdFeB magnets, and is easy to diffuse on the surface and inside of the magnet, thereby improving the diffusion effect. Attaching the attachment to copper or copper alloy foil can optimize the composition of the diffusion source, facilitate zonal diffusion, reduce the diffusion temperature, and improve the activity of the diffusion source. The diffusion source of the present invention can effectively improve the coercive force of the magnet under the premise of reducing the amount of rare earth elements used, and has little effect on the remanence, maximum magnetic energy product and squareness of the magnet.
[0064] <Method for preparing diffusion source>
[0065] The method for preparing a diffusion source of the present invention comprises the following steps: (A) preparing a support; and (B) obtaining a diffusion source.
[0066] Steps for preparing the load
[0067] The invention coats diffusion source slurry containing rare earth particles, non-rare earth oxides, non-rare earth metals or alloys, adhesives and organic solvents on the upper and lower surfaces of copper or copper alloy foil to obtain a load.
[0068] In some embodiments, the method further comprises the step of preparing a diffusion source slurry: mixing rare earth particles, non-rare earth oxides, non-rare earth metals or alloys, a binder and an organic solvent to obtain a diffusion source slurry.
[0069] The selection and dosage of rare earth particles, non-rare earth oxides, non-rare earth metals or alloys are as described above and will not be repeated here.
[0070] The binder can be selected from one or more of thermosetting resins, thermoplastic resins, synthetic rubbers, polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyimide (PI), and polyvinyl pyrrolidone (PVP). Examples of thermosetting resins include, but are not limited to, epoxy resins, phenolic resins, urea-formaldehyde resins, and polyurethanes. Examples of thermoplastic resins include, but are not limited to, polyvinyl acetals and perchlorethylene. Examples of synthetic rubbers include, but are not limited to, styrene-butadiene rubber, chloroprene rubber, and nitrile rubber. According to one embodiment of the present invention, the binder is an epoxy resin. For example, E44 type epoxy resin.
[0071] The amount of the binder used may be 1 to 3 parts by weight; preferably 1.5 to 2.5 parts by weight.
[0072] The organic solvent can be selected from one or more of p-methoxybenzyl alcohol, diethylene glycol butyl ether acetate, ethylene glycol diacetate, ethylene glycol ethyl ether acetate, tributyl citrate, α-terpineol, ethanol, acetone, petroleum ether, isopropanol, and ethyl acetate.
[0073] The amount of the organic solvent used may be 10 to 30 parts by weight; preferably 15 to 25 parts by weight.
[0074] The thickness of the support may be 30 to 150 μm, preferably 50 to 100 μm. In certain embodiments, the thickness of the support is 60 to 80 μm.
[0075] The copper or copper alloy foil may be cleaned before use. Specifically, the copper or copper alloy foil is ultrasonically treated in a small molecule monohydric alcohol to obtain a clean copper or copper alloy foil. The small molecule monohydric alcohol may be a monohydric alcohol containing 1 to 6 carbon atoms; preferably a monohydric alcohol containing 1 to 3 carbon atoms. For example, methanol, ethanol, propanol, isopropanol.
[0076] Steps to get the diffusion source
[0077] The present invention applies pressure to the upper surface and the lower surface of the load and heat-treats the load to obtain a diffusion source.
[0078] In certain embodiments, while applying 5-80 MPa to the upper and lower surfaces of the support, the support is cured at 80-160° C. for 1-7 min to obtain a diffusion source.
[0079] Preferably, the pressure applied to the upper and lower surfaces of the load is 10 to 50 MPa; more preferably, 20 to 30 MPa.
[0080] The curing temperature is preferably 100-140° C., and more preferably 120-130° C. Preferably, infrared heating is used to achieve the above curing temperature.
[0081] The curing time is preferably 2 to 5 minutes; more preferably 3 to 4 minutes.
[0082] This can improve the tightness of the bonding between the attached object and the metal foil, reduce the porosity, and ensure the integrity and uniformity of the load.
[0083] In certain embodiments, while applying a pressure of 5 to 80 MPa to the upper and lower surfaces of the support, the support is cured at 80 to 160° C. for 1 to 7 minutes to obtain a solidified material; and the solidified material is degreased at 230 to 290° C. for 15 to 90 minutes to obtain a diffusion source.
[0084] Preferably, the pressure applied to the upper and lower surfaces of the load is 10 to 50 MPa; more preferably, 20 to 30 MPa.
[0085] The curing temperature is preferably 100-140° C., and more preferably 120-130° C. Preferably, infrared heating is used to achieve the above curing temperature.
[0086] The curing time is preferably 2 to 5 minutes; more preferably 3 to 4 minutes.
[0087] The degreasing temperature may be 180-320° C., preferably 200-280° C., and more preferably 220-260° C. Preferably, infrared heating is used to achieve the above degreasing temperature.
[0088] The degreasing time may be 15 to 90 min, preferably 30 to 70 min, and more preferably 40 to 60 min.
[0089] Degreasing under the above conditions can remove some non-metallic elements introduced by the solvent and / or binder, such as carbon and other elements. The present invention has found that if some non-metallic elements introduced by the solvent and / or binder exist too much in the diffusion source, it will affect the performance of the magnet after diffusion; if these non-metallic elements are retained too little, it will affect the activity of the diffusion source and be unfavorable to the diffusion.
[0090] Preferably, degreasing is performed while applying pressure to the upper and lower surfaces of the solidified object. The pressure applied to the upper and lower surfaces of the solidified object may be 1 to 10 MPa, preferably 3 to 8 MPa, and more preferably 5 to 7 MPa. This can further improve the tightness of the attachments and the metal foil, reduce the porosity, and ensure the integrity and uniformity of the diffusion source.
[0091] The thickness of the diffusion source may be 60% to 95% of the thickness of the support. In certain embodiments, the thickness of the diffusion source is 70% to 80% of the thickness of the support.
[0092] The preparation method is simple and easy to operate, uses less organic compounds, and the obtained diffusion source has a higher solid content. The attachments are tightly bonded to each other, the bonding strength between the attachments and the metal foil is high, and the attachments are evenly dispersed, which is conducive to improving the diffusion effect.
[0093] <How to Handle Magnets>
[0094] The magnet processing method of the present invention comprises the following steps: heating, diffusing and aging a NdFeB magnet having at least a portion of its surface covered with the above-mentioned diffusion source to obtain a treated magnet. Preferably, the NdFeB magnet is a sintered NdFeB magnet. The diffusion source is specifically as described above and will not be described in detail herein. The heating, diffusing and aging treatments can be performed in a vacuum heat treatment furnace.
[0095] The diffusion source may be covered on the upper surface of the NdFeB magnet, may be covered on the lower surface of the NdFeB magnet, or may be covered on both the upper surface and the lower surface of the NdFeB magnet.
[0096] The surface of the NdFeB magnet may be covered with a single layer of diffusion source or multiple layers of diffusion source, and the multiple layers of diffusion source may be the same or different.
[0097] NdFeB magnets may contain neodymium, praseodymium, cobalt, copper, aluminum, zirconium, titanium, gallium, boron and iron. In certain embodiments, they may also contain dysprosium.
[0098] The content of neodymium may be 15 to 25 parts by weight, preferably 18 to 23 parts by weight. The content of praseodymium may be 3 to 10 parts by weight, preferably 5 to 8 parts by weight. The content of cobalt may be 0.2 to 5 parts by weight, preferably 0.5 to 1.5 parts by weight. The content of copper may be 0.1 to 0.8 parts by weight, preferably 0.2 to 0.5 parts by weight. The content of aluminum may be 0.05 to 1.2 parts by weight, preferably 0.08 to 1 parts by weight. The content of zirconium may be 0.05 to 0.8 parts by weight, preferably 0.1 to 0.5 parts by weight. The content of titanium may be 0.03 to 0.8 parts by weight, preferably 0.1 to 0.5 parts by weight. The content of gallium may be 0.05 to 0.5 parts by weight, preferably 0.1 to 0.3 parts by weight. The content of boron may be 0.7 to 0.98 parts by weight, preferably 0.85 to 0.95 parts by weight. The content of iron may be 65 to 68 parts by weight, preferably 66 to 67.5 parts by weight. The content of dysprosium may be 1 to 8 parts by weight, preferably 3 to 6 parts by weight.
[0099] The oxygen content in the NdFeB magnet may be 400 to 800 ppm, preferably 500 to 700 ppm.
[0100] The NdFeB magnet can be cylindrical, cube, cuboid, or irregular in shape. The thickness of the NdFeB magnet can be 1 to 25 mm, preferably 5 to 15 mm. The diameter of the NdFeB magnet can be 3 to 20 mm, preferably 5 to 15 mm.
[0101] The heating diffusion can be carried out under the condition of pressure <10Pa; preferably, under the condition of pressure <5Pa; more preferably, under the condition of pressure 10 -3 ~10 -4 Pa.
[0102] The heating diffusion can be performed in multiple stages. In some embodiments, the NdFeB magnet, at least a portion of which is covered with the above-mentioned diffusion source, is subjected to primary diffusion and secondary diffusion in sequence. In other embodiments, a pre-diffusion is performed before the primary diffusion.
[0103] The primary diffusion temperature may be 600 to 900°C, preferably 650 to 850°C. In some embodiments, the primary diffusion temperature is 700 to 800°C. The primary diffusion time may be 60 to 240 min, preferably 90 to 200 min. In some embodiments, the primary diffusion time is 120 to 150 min. The heating rate to the primary diffusion temperature may be 1 to 20°C / min, preferably 5 to 12°C / min.
[0104] The secondary diffusion temperature may be 850-960°C, preferably 880-920°C. In some embodiments, the secondary diffusion temperature is 890-900°C. The secondary diffusion time may be 200-500 min, preferably 240-480 min. In some embodiments, the secondary diffusion time is 300-400 min. The secondary diffusion temperature is greater than the primary diffusion temperature.
[0105] The pre-diffusion temperature may be 250 to 480°C, preferably 300 to 400°C, and more preferably 320 to 380°C. The pre-diffusion time may be 20 to 100 min, preferably 40 to 90 min, and more preferably 60 to 80 min. The heating rate to the pre-diffusion temperature may be 1 to 15°C / min, and preferably 3 to 8°C / min.
[0106] The magnet obtained by the diffusion treatment can be cooled to room temperature (20 to 35° C.) to obtain a diffused magnet.
[0107] The diffused magnet is subjected to aging treatment to obtain a treated magnet.
[0108] The aging treatment can be carried out at a pressure of less than 10 Pa; preferably, at a pressure of less than 5 Pa; more preferably, at a pressure of 10 -3 ~10 -4 Pa.
[0109] The aging treatment temperature may be 450 to 620°C, preferably 480 to 600°C, more preferably 500 to 560°C, and most preferably 510 to 520°C. The aging treatment time may be 60 to 300 min, preferably 100 to 250 min. In certain embodiments, the aging treatment time is 150 to 200 min. The heating rate to the aging treatment temperature may be 1 to 15°C / min, preferably 3 to 10°C / min.
[0110] Here is the test method:
[0111] Magnetic properties: Tested using NIM-10000HC permanent magnet tester. Test temperature 20°C. Test standard GB / T 3217:2013.
[0112] Embodiments 1 to 5
[0113] The dense and non-porous copper foil is ultrasonically treated in anhydrous ethanol to remove pollutants on the surface of the copper foil to obtain a clean copper foil. Rare earth particles, aluminum oxide, non-rare earth metal or alloy, binder and organic solvent are mixed to obtain a diffusion source slurry.
[0114] The diffusion source slurry was evenly coated on the upper and lower surfaces of the clean copper foil to obtain a load. A roller press was used to apply a pressure of 25 MPa to the upper and lower surfaces of the load, and the load was infrared heated and cured at 120°C for 3 minutes to obtain a cured product. A roller press was used to apply a pressure of 6 MPa to the upper and lower surfaces of the cured product, and the cured product was degreased at 260°C for 45 minutes to obtain a diffusion source for NdFeB magnets.
[0115] The raw materials and parameters are shown in Table 1.
[0116] Table 1
[0117]
[0118] Note: In terbium aluminum alloy, the content of terbium element is 96wt% and the content of aluminum element is 4wt%;
[0119] In the praseodymium-terbium-aluminum alloy, the content of praseodymium element is 65.5wt%, the content of terbium element is 30wt%, and the content of aluminum element is 4.5wt%;
[0120] In the praseodymium-dysprosium-aluminum alloy, the content of praseodymium element is 26wt%, the content of dysprosium element is 68wt%, and the content of aluminum element is 6wt%;
[0121] In the aluminum-zinc alloy, the content of zinc is 64wt% and the content of aluminum is 36wt%;
[0122] In the aluminum-cobalt alloy, the content of cobalt element is 78wt% and the content of aluminum element is 22wt%;
[0123] In the aluminum-silicon alloy, the content of silicon is 15wt% and the content of aluminum is 85wt%;
[0124] In the aluminum-magnesium alloy, the content of aluminum is 54wt%, and the content of magnesium is 46wt%.
[0125] Embodiments 6 to 10
[0126] The diffusion source was covered on the upper surface of the sintered NdFeB magnet (10 mm in diameter and 5 mm in thickness), and then multi-stage diffusion was performed in a vacuum heat treatment furnace; after cooling to 26°C, the diffused magnet was obtained. During the heating and diffusion process, the pressure in the furnace was 10 -3 ~10 -4 The composition of the sintered NdFeB magnet, the selection of diffusion sources and the diffusion conditions are shown in Table 2.
[0127] Table 2
[0128]
[0129] Note: “—” for pre-diffusion temperature and pre-diffusion time means no pre-diffusion is performed and primary diffusion is performed directly.
[0130] The diffused magnet is placed at a pressure ≤ 10 -3 Pa, aging treatment is carried out, and then rapid cooling is performed to 26° C. to obtain a treated magnet. The aging treatment is carried out in a vacuum heat treatment furnace.
[0131] The specific parameters of the aging treatment are shown in Table 3. The magnetic properties of the NdFeB magnet and the treated magnet are shown in Table 4.
[0132] Table 3
[0133]
[0134] Table 4
[0135]
[0136] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A diffusion source for NdFeB magnets, characterized in that: The diffusion source includes copper or copper alloy foil and attachments, the attachments are attached to the upper surface and the lower surface of the copper or copper alloy foil respectively, and the attachments include rare earth particles, non-rare earth oxides and non-rare earth metals or alloys; The rare earth element in the rare earth particles is selected from one or more of terbium, dysprosium, praseodymium, and neodymium, and contains at least one of terbium and dysprosium; the rare earth particles are selected from one or more of rare earth hydride particles, rare earth fluoride particles, rare earth single substance particles, and rare earth alloy particles; the content of the rare earth particles is 10 to 30 parts by weight; The non-rare earth oxide is selected from one or more of aluminum oxide and magnesium oxide; the content of the non-rare earth oxide is 0.1 to 5 parts by weight; The non-rare earth element in the non-rare earth metal or alloy is selected from one or more of copper, aluminum, magnesium, iron, zirconium, niobium, gallium, zinc, cobalt, and silicon, and the non-rare earth metal or alloy contains at least one of copper and aluminum; the amount of the non-rare earth metal or alloy is 0.3 to 5 parts by weight.
2. The diffusion source according to claim 1, characterized in that: The total content of terbium and dysprosium in the rare earth particles is greater than or equal to 12wt%, and the total content of rare earth elements is greater than or equal to 42wt%; The total content of copper and aluminum in the non-rare earth metal or alloy is greater than or equal to 15 wt %.
3. The diffusion source according to claim 1, characterized in that: The copper or copper alloy foil has a thickness of 1 to 100 μm; The rare earth particles have a D 50 The particle size of the non-rare earth oxide is 200-450 mesh, and the D 50 1~20μm.
4. The diffusion source according to claim 1, characterized in that: The rare earth particles contain non-rare earth metal elements, and the non-rare earth metal elements are selected from one or more of copper and aluminum.
5. The method for preparing a diffusion source according to any one of claims 1 to 4, characterized in that: The steps include: (1) coating a diffusion source slurry containing rare earth particles, non-rare earth oxides, non-rare earth metals or alloys, a binder and an organic solvent on the upper surface and the lower surface of a copper or copper alloy foil to obtain a supported material; (2) The supported object is heat treated while applying pressure to the upper and lower surfaces of the supported object to obtain a diffusion source.
6. The preparation method according to claim 5, characterized in that: Step (2) comprises the following steps: While applying a pressure of 5 to 80 MPa to the upper and lower surfaces of the supported object, the supported object is cured at 80 to 160° C. for 1 to 7 minutes to obtain a diffusion source.
7. The preparation method according to claim 5, characterized in that: Step (2) comprises the following steps: While applying a pressure of 5 to 80 MPa to the upper and lower surfaces of the load, the load is cured at 80 to 160° C. for 1 to 7 minutes to obtain a cured product; the cured product is degreased at 230 to 290° C. for 15 to 90 minutes to obtain a diffusion source.
8. The preparation method according to claim 7, characterized in that: While applying a pressure of 1 to 10 MPa to the upper and lower surfaces of the solidified object, the solidified object is degreased at 230 to 290° C. for 15 to 90 minutes to obtain a diffusion source.
9. The preparation method according to claim 8, characterized in that: The thickness of the support is 30-150 μm; the thickness of the diffusion source is 60%-95% of the thickness of the support.
10. A method for processing a neodymium iron boron magnet, characterized in that: The steps include: Performing heating diffusion and aging treatment on a NdFeB magnet at least a portion of the surface of which is covered with the diffusion source according to any one of claims 1 to 4 to obtain a treated magnet; The heating diffusion conditions are as follows: the primary diffusion temperature is 600-900°C, the primary diffusion time is 60-240min, the secondary diffusion temperature is 850-960°C, and the secondary diffusion time is 200-500min; and optionally, pre-diffusion is performed before the primary diffusion, the pre-diffusion temperature is 250 to 480° C., and the pre-diffusion time is 10 to 100 minutes; The aging treatment conditions are as follows: the aging treatment temperature is 450-620°C, and the aging treatment time is 80-350min.
Citation Information
Cited By
Anti-corrosion neodymium iron boron magnetic material and preparation process thereof
CN119943567A
A corrosion-resistant NdFeB magnetic material and its preparation process
CN119943567B